2022
DOI: 10.37899/journallamedihealtico.v3i1.624
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge Level of Adolescent Red Cross Students in First Aid for Syncope Handling

Abstract: Syncope is a temporary loss of consciousness consequence hypoperfusion cerebral global transient characterized with onset fast, duration which short and recovery spontaneous. Lost consciousness due to decreased blood flow to system Activation reticular and no need therapy electricity or chemistry for back to normal . The purpose of this study was to determine the level of knowledge of Adolescent Red Cross (PMR) students in first aid for handling syncope at SMA Negeri 1 Telaga Biru . This study uses a quantitat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Considering the increase in melatonin concentration observed (Table 1), it was suggested that the syncope induced by sleep disturbance could be linked to serum melatonin level. Furthermore serum melatonin concentrations were performed 24hours and 48hours (daytime and peak night) post syncope phenomenon to compare the various melatonin levels with reference values (Table 2) as well as ascertain the involvement of serum melatonin Although the subject did not notice any warning signs before fainting as a result of sleep obstruction and no medical history was documented prior to this time; basic first aid as was described by [8,9] was the intervention measure employed.…”
Section: Case Presentationmentioning
confidence: 99%
“…Considering the increase in melatonin concentration observed (Table 1), it was suggested that the syncope induced by sleep disturbance could be linked to serum melatonin level. Furthermore serum melatonin concentrations were performed 24hours and 48hours (daytime and peak night) post syncope phenomenon to compare the various melatonin levels with reference values (Table 2) as well as ascertain the involvement of serum melatonin Although the subject did not notice any warning signs before fainting as a result of sleep obstruction and no medical history was documented prior to this time; basic first aid as was described by [8,9] was the intervention measure employed.…”
Section: Case Presentationmentioning
confidence: 99%